Groundwater Velocity Field: Stochastic Analysis Of Major Groundwater Flowpaths And Implications For Contaminant Transport Within The Ga East And Adentan Districts, Ghana - Hagan, G.B (University of Ghana, 2016)
The hydrogeological system of the Ga East and Adentan Districts of the Greater Accra Region of Ghana was studied using numerical modelling on the Groundwater Modelling System platform (version 10.0). Historical hydrogeological data and groundwater monitoring data on twenty wells drilled in 2012 were relied on in conceptualising the hydrogeological system of the study area. A single aquifer system made up of quartzite-schist formation was identified. The borehole logs reveal four lithologies, laterite, schist, quartzite, and clay. Subsequently, a calibrated steady-state groundwater flow model was developed for the terrain. The aquifer hydraulic conductivity estimates for about 90% of the terrain are lower than 15.0 m day−1. The observed outliers were attributable to the fractured and jointed quartzite within the weathered zone, which enhanced the conduits within the materials for rapid flow of groundwater. The estimated velocity field is in the range of 0.002 m day−1 to 11.2 m day−1, with about 90% of the area having velocities below 0.85 m day−1. The spatial distribution of the velocity field tied in well with the hydraulic conductivity field observed for the terrain. The estimated velocity field makes contaminant transport significant in the domain. For instance, contaminants/pollutants leached into the aquifer zone through recharge by rainfall from the landfill sited at Pantang will travel at approximately 0.85 m day−1 towards Oyarifa, Teiman and Ayimensa communities along an identified flowpath. Seven principal groundwater flowpaths were identified using the particle tracking technique. The travel times along the flowpaths from recharge to discharge locations ranged from 7 years to 833 years. The cross-section cutting technique revealed cases of local and intermediate flow systems, and identified potential recharge areas. The effective aquifer recharge through precipitation ranges from 2.70×10−5 m day−1 to 8.10×10−5 m day−1, representing 1.2% and 3.6% of the average annual precipitation in the area. The water budget shows that the flow system conserved mass, an indication that the flow model was indeed calibrated under steady-state conditions. The water budget also indicates that the current abstraction levels of groundwater can be sustained by recharge through rainfall to the aquifer system with minimal net drawdown in the hydraulic head. Stochastic simulations carried out on the calibrated model indicates that the model is unique for the aquifer recharge, hydraulic conductivity and hydraulic head. Three management scenarios which are centred on variations in groundwater recharge and abstraction were simulated to investigate the sustainability of the groundwater resource. The first scenario indicates that the existing recharge rates can sustain up to a three times increase in the current rates of abstraction of groundwater for both domestic and commercial purposes. The second scenario shows that, when the current rates of recharge decline by half or more, there would be considerable drawdown if the current abstraction rates were to be sustained solely by groundwater resource. The third scenario reveals that, with rainfall being the main source of recharge to the aquifer, a reduction in the current rainfall figures coupled with an increase in the current abstraction rates by three to five times would result in considerable drawdown.
Thesis (PhD)
Keywords: Groundwater Velocity; Field; Stochastic Analysis; Flowpaths; Implications; Contaminant Transport; Ga East; Adentan; Ghana